Awareness of Undergraduate Students towards COVID 19 Vaccine and their Willingness to be Vaccinated - Fatima Fadhil Saleh, Huda Abdulsalam Abdulrahman, (Pakistan Journal of Medical & Health Sciences, 2022)
In order to satisfactorily control the COVID-19 pandemic, the vaccination program against it must be successful, so the aim of this study was to assess the awareness and desire to vaccinate for undergraduate students and the factors that influence the levels of that knowledge. A cross-sectional study was conducted with the participation of 554 undergraduate students from September 19 to October 20, 2021 through online survey. It proved that the vaccination acceptance rate was high (84.1%) and that the majority of their family members are ready to receive the vaccination (64.3%). They also have good knowledge of the vaccine except for the belief in the safety of the vaccine (64.35%). We concluded that despite the belief that vaccines are not safe; the vaccination has been widely accepted. Health education and adequate information about immunizations are important to build confidence about immunizations among nursing students. Thus, the increased vaccination campaigns among nursing students make it one of the ways to combat this epidemic.